4
$\begingroup$

I am trying to prove that

$$\int_{\mathbb{R}} x e^{-x} \cdot e^{-e^{-x}-x} = 1 - \gamma$$ and

$$\int_{\mathbb{R}} x^2 e^{-x} \cdot e^{-e^{-x}-x} = \pi^2/6 - 2\gamma + \gamma^2$$

I have tried to attack the integral using all possible calculus laws, but it brings me nowhere. We have derived that $\int_{\mathbb{R}} x \cdot e^{-e^{-x}-x} = \gamma$

$\endgroup$
  • 1
    $\begingroup$ Could you show us what you've done? (as in not just tell us, but show us) $\endgroup$ – clathratus Mar 5 at 17:14
  • $\begingroup$ Also note that $$e^{a}\cdot e^{b}=e^{a+b}$$ $\endgroup$ – clathratus Mar 5 at 17:15
  • $\begingroup$ @clathratus I posted what I have done $\endgroup$ – Cebiş Mellim Mar 5 at 17:37
4
$\begingroup$

$$I(n)=\int_{-\infty}^\infty x^{n} e^{-x} e^{-e^{-x}-x}dx$$ Let $u=e^{-x}$, $x=-\ln(u)$, $du=-e^{-x}dx$ $$I(n)=-\int_\infty^0 (-\ln(u))^{n} ue^{-u}du=(-1)^n \int_0^\infty \ln^n(u)u e^{-u}du$$

Now the Gamma function is defined as $$\Gamma(s)=\int_0^\infty x^{s-1}e^{-x}dx$$ So $$\left(\frac{d}{ds}\right)^n\Gamma(s)=\int_0^\infty \ln^n(x) x^{s-1} e^{-x}dx$$ Thus $$I(n)=(-1)^n \left(\frac{d}{ds}\right)^n\Gamma(s)|_{s=2}$$ Now let $n=1,2$ to get the values of the two original integrals. It could help to know that $$\Gamma'(2)=-\gamma+H_1=1-\gamma$$ and that $$\psi_1(2)=\frac{\pi^2}{6}-1$$ where $\psi_1(s)$ is the Trigamma Function.

EDIT: $$\psi_1(s)=\left(\frac{d}{ds}\right)^2 \ln(\Gamma(s))=\frac{\Gamma(s)\Gamma''(s)-\left(\Gamma'(s)\right)^2}{\Gamma^2(s)}$$ Evaluating at $s=2$ we get $$\Gamma''(2)-\left(\Gamma'(2)\right)^2=\frac{\pi^2}{6}-1$$ So $$\Gamma''(2)=\frac{\pi^2}{6}-1 +\left(\Gamma'(2)\right)^2=\frac{\pi^2}{6}-1 +(1-\gamma)^2=\frac{\pi^2}{6}-2\gamma+\gamma^2$$

$\endgroup$
  • 1
    $\begingroup$ @CebişMellim Edited to include it, glad I could help. $\endgroup$ – aleden Mar 5 at 21:01
1
$\begingroup$

What I have done so far is:

First integral Denote $u(x) = xe^{-x}$ and $f(x) := e^{-e^{-x}-x}$, let $F(x)$ be the antiderivative of $f(x)$. Then \begin{align*} \int_{\mathbb{R}} x e^{-x} \cdot e^{-e^{-x}-x} &= \int_{\mathbb{R}} u(x)f(x) \end{align*} Intergration by parts yields \begin{align*} \hspace{1cm} &= - \int_{\mathbb{R}} u'(x)F(x) \end{align*} We have $u'(x) = e^{-x} - u(x)$; thus, \begin{align*} \hspace{3.5cm} &= - \int_{\mathbb{R}} [e^{-x} - u(x)]F(x)\\ &= - \int_{\mathbb{R}} e^{-x} F(x) + \int_{\mathbb{R}} u(x)F(x) \end{align*} At last note that $f(x) = e^{-x}F(x)$; hence \begin{align*} \hspace{2cm} &= - \int_{\mathbb{R}} f(x) + \int_{\mathbb{R}} xf(x)\\ &= - 1 + \gamma \end{align*}

$\endgroup$
  • 1
    $\begingroup$ What is $u(x)$? $\endgroup$ – clathratus Mar 5 at 17:39

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.